G239(P) Use of non-invasive respiratory support in children referred to a paediatric intensive care retrieval service. (25th October 2020) - Emedo, M; Ramnarayan, P
Abstract : Background: High flow nasal cannula (HFNC) is now a widely used mode of Non Invasive Respiratory Support (NRS) for children with respiratory distress. Objectives: To describe the trends in use of NRS for children referred to a paediatric intensive care transport service, and identify any associations between mode used and final retrieval status. Methods: Retrospective review of two grouped cohorts to capture any seasonal variability; referrals from December and May of 2012/2013 were compared with 2017/2018. Children on acute BIPAP/CPAP or HFNC were included for analysis. Ventilation mode, proportions retrieved and intubation rates were compared, as were demographics and indicators of disease severity. Results: In total 204 children were referred on NRS, most commonly with bronchiolitis, pneumonia or cardiac conditions. There was no significant difference in baseline disease severity between the cohorts, as determined by SpO2:FiO2 ratio (p = 0.07) or referrer rated respiratory distress. In the 2017/2018 time periods, 30% of all referrals received by the service were on NRS vs. 15% in 2012/2013. Of these NRS referrals, HFNC represented a larger proportion in 2017/2018 than in 2012/2013 (57 vs 17%). There was no significant difference in final retrieval status or rates of intubation for transfer according to mode of NRS used at time of referral (p = 0.57). Conclusion: In 2017/2018 NRS was used more frequently for children referred for retrieval, and HFNC was more commonly chosen to deliver this compared with 2012/2013. This rise in popularity of HFNC has not been associated with a larger proportion of referrals requiring retrieval, or more children eventually needing intubation for transport.